Mengenal New Psychoactive Substances (NPS): sebuah tinjauan pustaka - Ni Made Leni; Luh Nyoman Alit Aryani; I Wayan Westa (Intisari Sains Medis, 2021)
Drug abuse is a global phenomenon that is difficult to control. Until now, various types of narcotics have been distributed in many countries, one of which is New Psychoactive Substances (NPS). Despite its fast growing and massive spread, NPS is still a new substance, considering the little number of data recorded up to recent days. This also results in difficulty of NPS identification in toxicological samples . The use of NPS is associated with many health problems, which causes physical and psychological disturbance potentially more severe than ordinary narcotics. This review aims to summarize the existing literature on NPS that focuses on identifying the types of NPS substances and symptoms as well as the management which could be provided to the patients. Penyalahgunaan narkotika merupakan fenomena global yang sulit dikendalikan, hingga saat ini variasi narkotika telah beredar di begitu banyak negara salah satunya termasuk Zat Psikoaktif Baru atau New Psychoactive Substances (NPS).  Terlepas dari penyebarannya yang cepat dan masif, masih banyak orang yang belum memiliki pengetahuan akan NPS mengingat pendataan zat-zat ini masih sedikit dilakukan. Hal tersebut juga menyebabkan identifikasi NPS dalam sampel toksikologi masih sulit dilakukan. Padahal penggunaan NPS sering dikaitkan dengan masalah kesehatan, dimana efek yang ditimbulkan dapat menyebabkan gejala gangguan fisik dan psikologis yang lebih berat dibandingkan zat narkotika pada umumnya. Tinjauan ini dibuat untuk merangkum literatur yang ada mengenai NPS yang berfokus pada pengenalan jenis-jenis zat NPS serta gejala juga tatalaksana yang dapat diberikan pada pasien pengguna NPS.